Understanding Employee Performance through Work Engagement: Evidence from Distributive Justice and Work-Life Balance - Revinda Afi Cintia; Asep Gunawan; Harry safari Margapradja (Univiversitas Dr. Djar Wattiheluw, 2026)
This study examines the effects of distributive justice and work life balance on employee performance through the mediating role of work engagement among operational employees of SPX Express in Cirebon, Indonesia. Using a quantitative causal associative design, data were collected from 123 employees selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM) with SmartPLS 4.0. The results indicate that distributive justice and work life balance do not directly affect employee performance but significantly enhance work engagement, which subsequently improves performance. Work engagement fully mediates the relationships between organizational resources and employee performance. These findings emphasize the importance of work engagement as a psychological mechanism linking organizational practices to performance outcomes. This study contributes to Equity Theory and Job Demands–Resources Theory while providing practical implications for improving logistics employee performance through engagement based strategies.